INFORMATION PLATFORM OF AN ONLINE CLOTHING STORE WITH A VIRTUAL FITTING ROOM AS A COMPLEX SYSTEM - KONDRA, ARTUR; KUNANETS, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents the concept of an information platform for an online clothing store with a virtual fitting room as an example of a next-generation complex information system. The architecture of the platform is described, combining classical e-commerce tools with intelligent modules for personalized design, recommendation systems, and 3D/AR visualization technologies that ensure interactivity and a high level of user experience. The platform is characterized as a multi-layered and decentralized structure with a high degree of integration and dynamic interaction between modules, which enables adaptive data management, scalability, and flexibility of architectural solutions. An analysis is conducted of the system’s compliance with the criteria of complexity according to the theory of complex systems, in particular: nonlinearity, emergence, adaptability, self-organization, multi-level hierarchy, and decentralized control. It is demonstrated that the platform functions as an emergent ecosystem where user behavior, order dynamics, and adaptive algorithms generate new properties absent at the level of individual modules. Special attention is given to the system’s intelligent components: the recommendation module, based on machine learning methods and behavioral data analysis; the virtual fitting room module, which employs 3D modeling, AR technologies, and computer vision; and the personalized design module, which allows the generation of unique offers according to users’ style and anthropometric characteristics. The use of a mathematical model for quantitative evaluation of the system’s complexity and determination of integral performance indicators is substantiated. The article outlines the prospects for the development of such platforms in the context of digital fashion, personalized commerce, and the formation of new e-commerce business models oriented toward integration with smart city ecosystems, mobile applications, and decentralized financial services.